(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the institutional and functional aspects of the scientific management of society are revealed from a socio-philosophical point of view. Institutional and functional aspects of scientific management of society are implemented by the principles of sociality. The importance of the governance process carried out by the social institutions of the society has been researched.